Acute myeloid leukemia impairs natural killer cells through the formation of a deficient cytotoxic immunological synapse. Issue 10 (4th September 2014) - Khaznadar, Zena; Henry, Guylaine; Setterblad, Niclas; Agaugue, Sophie; Raffoux, Emmanuel; Boissel, Nicolas; Dombret, Hervé; Toubert, Antoine; Dulphy, Nicolas
<x xml:space="preserve">Abstract</x> Acute myeloid leukemia (AML) cells are killed by allogeneic NK cells. However, autologous NK cells from AML patients express decreased levels of activating receptors, and show reduced cytotoxicity. Here, we investigated how interactions between NK and AML cells might cause loss of NK‐cell activity in patients. Our results show that AML cell lines and primary blasts alter the NK‐cell phenotype, reducing their cytotoxic potential upon prolonged contact. Downregulation of NK‐cell‐activating receptors was contact‐dependent and correlated with conjugate formation. Time‐lapse imaging of HL60 AML cell line and NK‐cell interactions showed a high proportion of noncytolytic contacts. Studies of NK‐cell immunological synapses revealed a defect in lytic synapse formation. Namely, despite correct F‐actin and LFA‐1 recruitment, polarization of lytic granules toward primary blasts or AML cell lines was reduced. The NK–AML cell line synapses showed impairment of CD3ζ recruitment. Attempts to correct these synapse defects by cytokine stimulation of NK cells improved conjugate formation, but not granule polarization. Pretreatment of AML cell lines with the immunomodulating molecule lenalidomide significantly enhanced granule polarization. We speculate that combining immunomodulatory drugs and cytokines could increase AML cell sensitivity to autologous NK cells and reinforce the activity of allogeneic NK cells in adoptive immunotherapy.